Quality Attributes of Pork Patties Wrapped with Polyphenol Nano solutions Incorporated Sodium Alginate Films at Refrigerated Storage (4±1 0C) - Rao, V. Giridhara; Mallika, E. Naga; Rao, B. Eswara; Rao, T. Srinivasa (International Journal of Livestock Research, 2021)
The study was aimed at evaluating the efficacy of edible film wraps prepared with Quercetin and Tannic acid nanosolution loaded sodium alginate on the quality and shelf-life of pork patties at refrigerated storage (4±1 0C). The films with Tannic acid had higher physical strength and quality than the films with Quercetin in terms of tensile strength, elongation at break, water vapour permeability, water sorption, light transmission, antioxidant activity, antimicrobial activity and total phenol content than films with Quercetin. The quality of pork patties wrapped with the above films was compared throughout the storage period. The patties wrapped with Tannic acid nanosolution incorporated film had lower cooking loss, pH, TBARS, Total Plate Count and Yeast and Mould Count compared to their counterparts. The results revealed that the use of natural polyphenols in nanosolution form in edible packaging offers a great advantage to maintain the quality of the product.